Inter-State Variation in Neonatal Mortality Rate Among Indian States - Tushar A Patel; Deepak B Sharma (Medsci Publications, 2013)
Background: Infant Mortality Rate has been accepted as an important indicator of overall health status of community and has also been included in millennium development goal indicators. The study was conducted to find the: Association of neonatal mortality rate with different risk factors and association of neonatal mortality rate with various interventional variables Methods: This study uses data from Indian National Family Health Survey -3 (NFHS-3). Sample for analysis includes all 29 states of India in which third round of National Family Health Survey were conducted and reports for the same were available. Data was obtained from state reports of National Family Health Survey -3.Neonatal mortality rates of different states were taken as dependent variable. Results: Bi-variate regression showing influence of percentage of women age 15-19 years who have begun childbearing and percentage of women with BMI < 17 on neonatal mortality was confounding effect of socio-economic status. Bi-variate regression showing influence of ante-natal check up, iron-folic acid supplementation and post natal check up on neonatal mortality was confounding effect of socio-economic status. Conclusions and Recommendations: The only variable other than socio-economic condition which was having association with neonatal mortality rate was percentage of hospital delivery. Government of India should take all possible measures to make health care services particularly facility based services available, accessible and affordable.